Customer Experiences: A New Perspective for Quality Services in Universities - Shoaib, Haneen (The Arab Journal of Administration, 2021)
The study aims to define the role of customer experiences management in improving the quality of services in Universities, and to raise awareness of the importance of managing customer experiences in improving quality. Moreover, it determines the impact of the application on improving the quality of services faculty members’ perspective. The Study Found: There is a statistically significant effect, at a level of significance less than (a ≥ 0.05), for Universities to use customer experience management to improve service quality. Customer electronic experiences are used incorrectly. A template that combines traditional and electronic systems must be created. The University administration does not allow the participation of lower level employees when planning to implement the new regulations. It is not important to have an organizational unit to manage customer experiences in the organizations, because success depends on the integrity of the application. The application does not differ according to the type of Universities due to the similarity of the organizational aspects amongst them. The Study Recommends: The necessity of activating the role of organizational culture, targeting the clients more holistically, and benefiting from their experiences. The necessity of using remote e-learning programs, especially during the Corona (Covid-19) pandemic situation. It is necessary to constantly support the trademark and brand name by positioning it in the minds of customers. To ensure that the relationship with the customers more emotional, and to provide them with good emotional experiences